Landscape of Immune Cells Heterogeneity in Liver Transplantation by Single-Cell RNA Sequencing Analysis - Li, Xinqiang; Li, Shipeng; Wu, Bin; Xu, Qingguo; Teng, Dahong; Yang, Tongwang; Sun, Yandong; Zhao, Yang; Li, Tianxiang; Liu, Dan; Yang, Shuang; Gong, Weihua; et al. (Frontiers in Immunology, 2022)
Rejection is still a critical barrier to the long-term survival of graft after liver transplantation, requiring clinicians to unveil the underlying mechanism of liver transplant rejection. It remains unclear that cellular diversity and the interplay between immune cells in the liver graft microenvironment. Herein, we performed single-cell RNA sequencing analysis to delineate the landscape of immune cells heterogeneity in liver transplantation. T cells, NK cells, B cells, myeloid cell subsets in human liver and blood were enriched to characterize their tissue distribution, gene expression and functional modules. The proportion of CCR6+CD4+ T cell increased within allograft suggesting that there are more memory CD4+ T cells after transplantation, in parallel with exhausted CTLA4+CD8+ T and actively proliferating MKI67+CD8+ T cells increased significantly, where they manifested heterogeneity, distinct function and homeostatic proliferation. Remarkably, the changes of CD1c+ DC, CADM+ DC, MDSC and FOLR3+ Kupffer cells increase significantly, but the proportion of CD163+ Kupffer, APOE+ Kupffer, and GZMA+ Kupffer decreased. Furthermore, we identified LDLR as a novel marker of activated MDSC to prevent liver transplant rejection. Intriguingly, a subset of CD4+CD8+FOXP3+ T cells included in CTLA4+CD8+ T cells was firstly detected in human liver transplantation. Furthermore, intercellular communication and gene regulatory analysis implicated the LDLR+ MDSC and CTLA4+CD8+ T cells interact through TIGIT-NECTIN2 signaling pathway. Taken together, these findings have gained novel mechanistic insights for understanding the immune landscape in liver transplantation, and it outlines the characteristics of immune cells and in particular provides potential therapeutic targets in liver transplant rejection.